Antiviral Therapeutics: Graphene Oxide Nanosheets Interact and Interfere with SARS‐CoV‐2 Surface Proteins and Cell Receptors to Inhibit Infectivity (Small 25/2021). Issue 25 (24th June 2021) - Unal, Mehmet Altay; Bayrakdar, Fatma; Nazir, Hasan; Besbinar, Omur; Gurcan, Cansu; Lozano, Neus; Arellano, Luis M.; Yalcin, Süleyman; Panatli, Oguzhan; Celik, Dogantan; Alkaya, Damla; Agan, Aydan; et al.
Abstract : In article number 2101483, Kostas Kostarelos, Açelya Yilmazer, and co‐workers report that thin, biological‐grade graphene oxide (GO) nanosheets show molecular affinity toward the SARS‐CoV‐2 viral spike and the ACE2‐bound spike complex. GO nanosheets were shown to inhibit the infection of wild‐type SARS‐CoV‐2 experimentally in cell cultures. Through an interplay of molecular dynamics simulations and cell biology, this work demonstrates that graphene oxide sheets could offer a platform to effectively interact and potentially transport other molecules to inactivate SARS‐CoV‐2.